A Side-Channel-Aware Cryptographic Framework for Secure Interactive, Embedded, IoT, and Edge Communication Systems - Walid W. Souror; Mohamed Fouad; Fahmi Khalif; Ali E. Takieldeen (Universitas Dian Nuswantoro, 2026)
Secure interactive, embedded, and edge communication systems are often deployed in physically exposed environments where algorithmically secure ciphers may exhibit implementation-specific leakage. This paper presents a simulation-based evaluation of a configurable hybrid AES-Blowfish framework comprising AES-Hybridization, Combined Blowfish Trilogy, and cascaded Blowfish-to-AES modes. The AES-Hybridization path combines AES-256-CBC, Argon2id-derived whitening material, HMAC-based integrity binding, plaintext masking, and modeled randomized hiding activity. The hiding activity is represented solely within the leakage simulation and does not modify the plaintext or ciphertext. The Blowfish path employs session-dependent P-array randomization, dynamic S-box initialization, and a three-stage Feistel-like structure. The framework is evaluated using representative IoT/edge workload proxies, component-level ablation studies, modeled leakage assessment, non-ideal leakage scenarios, parameter-sensitivity analysis, and a software-level performance model. Compared with the simulated baseline configurations, the proposed modes reduce modeled TVLA, CPA, and DPA distinguishability, with AES-Hybridization providing the most balanced security-performance trade-off and the cascaded mode achieving the lowest modeled distinguishability at the highest computational cost. All findings are derived exclusively from simulation; no validation using physical power traces, electromagnetic traces, FPGA implementations, or microcontroller platforms is claimed.